Touch stimulated pulse generation in biomimetic single-layer graphene. Issue 6 (21st January 2016) - Sul, Onejae; Chun, Hyunsuk; Choi, Eunseok; Choi, Jungbong; Cho, Kyeongwon; Jang, Dongpyo; Chun, Sungwoo; Park, Wanjun; Lee, Seung-Beck
Abstract : We report on a novel single-layer graphene based artificial mechanoreceptor that generates a resistance pulse as the contact stimulus passes a specific threshold pressure, mimicking the generation of action potentials in a biological fast-adapting mechanoreceptor. Abstract : Detecting variation in contact pressure is a separate sensing mode in the human somatosensory system that differs from the detection of pressure magnitude. If pressure magnitude and variation sensing can be achieved simultaneously, an advanced biomimetic tactile system that better emulates human senses may be developed. We report on a novel single-layer graphene based artificial mechanoreceptor that generates a resistance pulse as the contact stimulus passes a specific threshold pressure, mimicking the generation of action potentials in a biological fast-adapting mechanoreceptor. The electric field from a flexible membrane gate electrode placed above a graphene channel raises the Fermi level from the valence band as pressure deflects the membrane. The threshold pressure is reached when the Fermi level crosses the Dirac point in the graphene energy band, which generates a sharp peak in the measured resistance. We found that by changing the gate potential it was possible to modulate the threshold pressure and using a series of graphene channels, a train of pulses were generated during a transient pressurizing stimulus demonstrating biomimetic behaviour.